Ulcerative Gastritis and Esophagitis in Two Children with Sarcina ventriculi Infection - de Meij, Tim G. J.; van Wijk, Michiel P.; Mookhoek, Aart; Budding, Andries E. (Frontiers in Medicine, 2017)
Sarcina ventriculi is a Gram-positive, obligate anaerobic coccus, with a characteristic morphology. Only 22 cases of human infections by this micro-organism, including seven in children, have been reported in literature so far. Affected subjects usually present with abdominal pain, nausea, vomiting and delayed gastric emptying. However, life-threatening complications, like emphysematous gastritis and gastric perforation have also been described. Gastroparesis and gastric outlet obstruction have been considered as a potential etiologic factor. All paediatric cases described thus far presented with concomitant gastro-intestinal pathology, such as Helicobacter pylori gastritis, celiac disease, infection with Giardia lamblia or Candida spp. Here, we report two children with Sarcina ventriculi infection, in whom the diagnosis was established by typical histological findings in mucosal biopsies. The first child presented with hematemesis due to ulcerative esophagitis and gastritis, the second child with a history of esophageal stricture had ulcerative gastritis. Confirmation of Sarcina ventriculi infection is feasible by molecular microbiota detection methods, since this microorganism cannot be detected by classical culture techniques. Prompt treatment with antibiotics could prevent life-threatening complications.